2011
DOI: 10.1097/fch.0b013e31820e0d47
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian and Bicycle Planning in Rural Communities

Abstract: Pedestrian and bicycle planning has traditionally been viewed from an urban design perspective, rather than a rural or regional planning perspective. This study examined the prevalence and quality of pedestrian and bicycle plans in North Carolina according to geography, regional planning, and sociodemographics. Plan prevalence was lower, but plan quality tended to be higher, in rural areas compared with urban areas. Correlations between plan prevalence and active commuting were strongest in lower-income rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Additionally, the built environment is often seen as an amenity rather than a necessity by rural community members [93]. Therefore, strong public participation and buy-in, collaboration, and input are needed from community members and leaders, partners, and stakeholders [93][94][95], including mayors, town planners, public works departments, recreation department staff, school officials, church leaders, business owners, health care and public health professionals, architects, parents, senior citizens, and youth.…”
Section: Partnershipsmentioning
confidence: 98%
“…Additionally, the built environment is often seen as an amenity rather than a necessity by rural community members [93]. Therefore, strong public participation and buy-in, collaboration, and input are needed from community members and leaders, partners, and stakeholders [93][94][95], including mayors, town planners, public works departments, recreation department staff, school officials, church leaders, business owners, health care and public health professionals, architects, parents, senior citizens, and youth.…”
Section: Partnershipsmentioning
confidence: 98%
“…Dukeshire & Thurlow [ 38 ] reported rural communities face significant challenges in the policy arena such as: lack of understanding of the policy process; lack of community resources, education and training; and lack of access to information such as research. Further, Aytur et al [ 40 ] found public health practitioners were less involved in rural planning processes than urban ones. However, the current study suggests public health professionals and community partners are participating in the policy process as it relates to planning documents in rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…11 Interventions to improve child health that draw upon and extend community partnerships can promote healthy lifestyles and also raise awareness for health-related careers. 15 National objectives have been set for improving the health of Americans in rural communities. 13 A community-wide health and wellness coalition which spurs a coordinated effort in many different sectors (eg, health, schools, community, government) can have a transformative effort.…”
mentioning
confidence: 99%